Astropectinidae (Asteroidea) diversity in the Mar del Plata Submarine Canyon: A deep-water exploration - Rivadeneira, Pamela Ruth (2025)
The family Astropectinidae is one of the most diverse and numerous families of sea stars found in deep waters, particularly well-represented in the Atlantic Ocean. This family comprises 26 genera, with species inhabiting environments ranging from shallow coastal zones to abyssal depths. In this study, the Mar del Plata Submarine Canyon, located off the coast of Argentina, was explored at depths ranging from 200 to 3500 meters. A total of 153 specimens of Astropectinidae were collected, representing six species from five different genera. All species recorded are new occurrences for this region, including three new species described herein: Dytaster stellamarisae, Plutonaster neninae and Psilaster pearsei. Additionally, we report new regional observations of Bathybiaster loripes, Dytaster grandis, and Leptychaster kerguelenensis. These findings substantially expand the known distribution and diversity of Astropectinidae in the deep waters of the southwestern Atlantic.